Daily Remote Ischemic Conditioning Can Improve Cerebral Perfusion and Slow Arterial Progression of Adult Moyamoya Disease—A Randomized Controlled Study - Xu, Jiali; Zhang, Qian; Rajah, Gary B.; Zhao, Wenbo; Wu, Fang; Ding, Yuchuan; Zhang, Bowei; Guo, Wenting; Yang, Qi; Xing, Xiurong; Li, Sijie; Ji, Xunming (Frontiers in Neurology, 2022)
Background and Purpose Moyamoya disease (MMD) is a complicated cerebrovascular disease with recurrent ischemic or hemorrhagic events. This study aimed to prove the safety and efficacy of remote ischemic conditioning (RIC) on MMD. Methods In total, 34 patients with MMD participated in this pilot, prospective randomized controlled study for 1 year. 18 patients were allocated into the RIC group, and 16 patients accepted routine medical treatment only. RIC-related adverse events were recorded. The primary outcome was the improvement ratio of mean cerebral blood flow (mCBF) in middle cerebral artery territory measured by multidelay pseudocontinuous arterial spin labeling, and the secondary outcomes were the cumulative incidence of major adverse cerebrovascular events (MACEs), the prevalence of stenotic-occlusive progression, and periventricular anastomosis at 1-year follow-up. Results In total, 30 of the 34 patients with MMD completed the final follow-up (17 in the RIC group and 13 in the control group). No adverse events of RIC were observed. The mCBF improvement ratio of the RIC group was distinctively higher compared with the control group (mCBF−whole-brain: 0.16 ± 0.15 vs. −0.03 ± 0.13, p = 0.001). Stenotic-occlusive progression occurred in 11.8% hemispheres in the RIC group and 38.5% in the control group (p = 0.021). The incidence of MACE was 5.9% in the RIC group and 30.8% in the control group (hazard ratio with RIC, 0.174; 95% CI, 0.019–1.557; p = 0.118). No statistical difference was documented in the periventricular anastomosis between the two groups after treatment. Conclusions Remote ischemic conditioning has the potential to be a safe and effective adjunctive therapy for patients with MMD largely due to improving cerebral blood flow and slowing the arterial progression of the stenotic-occlusive lesions. These findings warrant future studies in larger trials.